"Just One Thing after Another": Recursive Cascades and Chronic Conditions. (30th June 2016) - Manderson, Lenore; Warren, Narelle
Abstract : Chronic conditions and their resultant difficulties in daily living frequently occur with other health problems, sometimes due to interactions or complications at a biological level, or as a result of common pathogens or risk factors. On other occasions, they develop independently. Drawing on research conducted with Australian women that began in the mid‐2000s and is still ongoing, we highlight how chronic structural factors shape the risk factors of "chronic" conditions, influencing health seeking, continuity of care, and health outcomes. Institutional, economic, and other circumstantial factors pertain and impact health trajectories as much in highly industrialized as in resource poor settings. In illustrating how poverty and social exclusion create the preconditions of multiple chronic health problems, and how chronic health problems increase such disadvantages for individuals and their households, we introduce the idea of "recursive cascades" to capture the often inevitable trajectory of increasing ill health and growing empoverishment.